2018
DOI: 10.1111/are.13678
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of soybean meal with Methylobacterium extorquens single-cell protein in feeds for rainbow trout (Oncorhynchus mykiss Walbaum)

Abstract: A feeding trial was conducted with juvenile rainbow trout (15-16 g initial weight) to assess the effects of including single-cell protein (SCP) produced from Methylobacterium extorquens in trout feeds. Three isonitrogenous and isoenergetic diets were produced: a control diet and two experimental diets containing 5% or 10% bacterial protein meal replacing soybean meal. Triplicate tanks, each containing 35 fish, were fed each diet to apparent satiation in a constant-temperature (15°C), flow-through tank system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…A study indicated that growth inhibition of rainbow trout fed SCP produced from M. extorquens was directly proportional to the reduction in feed intake (Hardy et al, 2018 Values are presented as mean ± SD (n = 6); values with different superscripts in the same row differ significantly (p < .05). A study indicated that growth inhibition of rainbow trout fed SCP produced from M. extorquens was directly proportional to the reduction in feed intake (Hardy et al, 2018 Values are presented as mean ± SD (n = 6); values with different superscripts in the same row differ significantly (p < .05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study indicated that growth inhibition of rainbow trout fed SCP produced from M. extorquens was directly proportional to the reduction in feed intake (Hardy et al, 2018 Values are presented as mean ± SD (n = 6); values with different superscripts in the same row differ significantly (p < .05). A study indicated that growth inhibition of rainbow trout fed SCP produced from M. extorquens was directly proportional to the reduction in feed intake (Hardy et al, 2018 Values are presented as mean ± SD (n = 6); values with different superscripts in the same row differ significantly (p < .05).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the studies on the use of SCP in aquafeeds suggested that palatability might be an important reason for the unsuitability of these SCP ingredients to replace fishmeal completely. A study indicated that growth inhibition of rainbow trout fed SCP produced from M. extorquens was directly proportional to the reduction in feed intake (Hardy et al, 2018 Values are presented as mean ± SD (n = 6); values with different superscripts in the same row differ significantly (p < .05). 2 Initial body weight (IBW, g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of alternative protein products in aquaculture diets is often limited by lower levels of digestible protein or issues with palatability. The use of SCP products is no exception, and in fact, a reduction to feed intake was believed to be a larger issue over the nutritional value of the diets (Hardy et al., 2018). In the current study, rainbow trout showed a similar acceptance of the feeds, with no leftover feed being observed in the tanks, while the apparent digestibility of SCP was generally high.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presence of ANF in other protein sources, such as cottonseed meal and rapeseed meal, was also shown to reduce the productivity of S. salar (Foroutani et al., 2018) and rainbow trout Oncorhynchus mykiss (Deng et al., 2014). Due to the sensitivity of salmonids to ANF, research is increasingly exploring the feasibility of using non‐plant‐based proteins as FM alternatives, which has included single cell proteins (SCP) from yeast (Rumsey, Hughes, Smith, Kinsella, & Shetty, 1991) or bacteria (Aas et al., 2006; Hardy, Patro, Pujol‐Baxley, Marx, & Feinberg, 2018; Perera, Carter, & Houlihan, 1995; Tlusty et al., 2017). In fact, SCP can be a more sustainable and readily available resource, particularly when cultured from nutrient‐rich effluent farm water.…”
Section: Introductionmentioning
confidence: 99%